Ethyl 5-amino-1-(4-chloro-2-nitrophenyl)-1H-pyrazole-4-carboxylate - Zia-ur-Rehman, Muhammad (International Union of Crystallography, 2009)
In the molecule of the title compound, C(12)H(11)ClN(4)O(4), the pyrazole ring is coplanar with the amino and ethoxycarbonyl groups within 0.026 (2) and 0.105 (2) Å, respectively. The C (6) ring of the 4-chloro-2-nitrophenyl group is twisted by 53.58 (4)° relative to the plane of the pyrazole ring. The planar structure of the pyrazole ring is stabilized by an intramolecular N—H⋯O hydrogen bond between its substituents. Neighbouring molecules are linked through intermolecular N—H⋯N and N—H⋯O hydrogen bonds, giving rise to one-dimensional tapes along the b axis. Molecules in the chain are linked to those of an adjacent chain through weak C—H⋯O interactions, forming a three-dimensional network.